2010
DOI: 10.1073/pnas.0911328107
|View full text |Cite
|
Sign up to set email alerts
|

Force-dependent polymorphism in type IV pili reveals hidden epitopes

Abstract: Through evolution, nature has produced exquisite nanometric structures, with features unrealized in the most advanced manmade devices. Type IV pili (Tfp) represent such a structure: 6-nmwide retractable filamentous appendages found in many bacteria, including human pathogens. Whereas the structure of Neisseria gonorrhoeae Tfp has been defined by conventional structural techniques, it remains difficult to explain the wide spectrum of functions associated with Tfp. Here we uncover a previously undescribed force-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
130
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(147 citation statements)
references
References 38 publications
17
130
0
Order By: Relevance
“…Yet Vibrio cholerae type IV pili are heterogeneous even without being subjected to mechanical shearing (44), and Neisseria gonorrhoeae type IV pili are not polymorphic although they were prepared by shearing (45). Interestingly, the N. gonorrhoeae type IV pili were shown to undergo a conformational change that exposed new epitopes when force was applied (46). Filament polymorphism implies structural plasticity, which would allow the pili to maintain adherence to the host epithelium when subjected to high flow forces.…”
Section: Resultsmentioning
confidence: 99%
“…Yet Vibrio cholerae type IV pili are heterogeneous even without being subjected to mechanical shearing (44), and Neisseria gonorrhoeae type IV pili are not polymorphic although they were prepared by shearing (45). Interestingly, the N. gonorrhoeae type IV pili were shown to undergo a conformational change that exposed new epitopes when force was applied (46). Filament polymorphism implies structural plasticity, which would allow the pili to maintain adherence to the host epithelium when subjected to high flow forces.…”
Section: Resultsmentioning
confidence: 99%
“…In Neisseria gonorrhea, TFP exhibit conformational changes upon stretching (28) and stretching reduces TFP width. Interestingly, these changes expose hidden PilA epitopes, indicating that PilA itself may change conformation upon tension.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, the deformations occur in localized regions, implying that there are multiple types of interactions that can occur between pilin subunits in a single intact fiber. The ability to stretch without breaking was suggested to provide a buffer against force fluctuations along the length of a fiber, preventing detachment during transient increases in shear forces (46). The ability to undergo deformation was recently linked to the presence of the Neisseria-specific minor pilin, PilX (63).…”
Section: Type IV Pilus Modelsmentioning
confidence: 99%
“…Interestingly, Biais and colleagues (46) demonstrated that the T4a pili of N. gonorrhoeae can undergo dramatic and reversible conformational changes upon application of threshold levels of force, stretching in their longer dimension to become ϳ40% narrower than unstretched pili, with a concomitant reduction of ϳ2/3 of the mass per unit length (Fig. 6).…”
Section: Type IV Pilus Modelsmentioning
confidence: 99%